Strategy document supported by UKAID and GIZ on gender and inclusion in social protection responses during COVID-19 - CGIAR Research Program on Policies, Institutions, and Markets (2020)
This document provides key considerations and examples of how gender and social inclusion can be integrated into potential COVID-19 response options/strategies via existing social protection and humanitarian programs.